Influence of parental behaviour, peer pressure and moderating role of religiosity and cultural values on juvenile delinquent behaviour: case of Punjab, Pakistan - Ashraf, Muhammad Umair (2021)
Juvenile delinquent behaviour becoming an emerging social problem for developed and developing countries, also impacting every segment of the society especially social institutions. The main objective of this study is to investigate the relationship between parental behaviour, peer pressure, and juvenile delinquent behaviour with moderating effect of religious commitment and cultural values among higher secondary school children in Punjab, Pakistan. This study is cross-sectional in nature and followed the survey method for the collection of data from 770 school children. The SPSS and SMART PLS 3.0 are used for the basic screening of the raw data and testing of hypothetical statements. The results of this study reveal that parental behaviour has a significant negative relationship with juvenile delinquent behaviour, while peer pressure has a significant positive association with juvenile delinquent behaviour. Religiosity and cultural values also have significant negative association with juvenile delinquent behaviour. The findings also reveal that religiosity moderates the relationship between peer pressure and juvenile delinquent behaviour, in contrast, religiosity does not moderate the relationship between parental behaviour and juvenile delinquent behaviour. However, cultural values do not moderate the relationship between parental behaviour, peer pressure, and juvenile delinquent behaviour. The findings of the present research are important for practitioners and policymakers to further understandings and coping strategies for the deterrence of juvenile delinquent behaviour. Finally, theoretical, methodological, and practical contribution of this study, as well as limitation and recommendation for future research are also adequately discussed in this study.